Self-assembly of class II hydrophobins on highly polar surfaces - Grunér, Mathias S. (My University, 2011)
Hydrophobins, adhesive proteins produced by filamentous fungi, have been described as the most surface active proteins known and show extraordinary properties regarding formation of surfaces. Hydrophobins have roles in the growth and development of the fungi including function in adhesion to surfaces, reducing surface tension for aerial growth and spore hydrophobicity and to aid spreading of aerial spores. Observations of filamentous fungi show that the structures formed by their mycelia can be very hydrophobic. Furthermore, airborne spores (conidia) covered with a surface layer of hydrophobin has been shown to mask the recognition of the conidia by the human immune system and hence prevents immune response. The knowledge of how hydrophobins aid in producing these fascinating properties is far from complete. This study aims to explain this by examining the abilities of the class II hydrophobins HFBI, HFBII and HFBIII to bind to submerged polar surfaces making them more hydrophobic, replicating the role hydrophobins have when forming hydrophobic surface coatings by self assembly on fungal spores and mycelia of filamentous fungi. It is shown here that binding onto submerged polar surfaces occurs by self assembly under specific conditions and that the binding can result in a significant increase in water contact angle of the surface, hence making it more hydrophobic.
Keywords: Livsvetenskaper; Industriell bioteknik; Life Science; Industrial Biotechnology